2021
DOI: 10.1002/ejhf.2201
|View full text |Cite
|
Sign up to set email alerts
|

The combination of carboxy‐terminal propeptide of procollagen type I blood levels and late gadolinium enhancement at cardiac magnetic resonance provides additional prognostic information in idiopathic dilated cardiomyopathy – A multilevel assessment of myocardial fibrosis in dilated cardiomyopathy

Abstract: We quantified fibrosis in 209 DCM patients at three levels: (i) non-invasive late gadolinium enhancement (LGE) at cardiac magnetic resonance (CMR); (ii) blood biomarkers [amino-terminal propeptide of procollagen type III (PIIINP) and carboxy-terminal propeptide of procollagen type I (PICP)], (iii) invasive endomyocardial biopsy (EMB) (collagen volume fraction, CVF). Both LGE and elevated blood PICP levels, but neither PIIINP nor CVF predicted a worse outcome defined as death, heart transplantation, heart failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 42 publications
0
30
2
Order By: Relevance
“…In a study including 209 patients with dilated cardiomyopathy, different markers of fibrosis were assessed. Late gadolinium enhancement at cardiovascular magnetic resonance and the biomarker carboxy‐terminal propeptide of procollagen type I had additive prognostic value 10 …”
Section: Diagnosis and Prognosismentioning
confidence: 97%
See 1 more Smart Citation
“…In a study including 209 patients with dilated cardiomyopathy, different markers of fibrosis were assessed. Late gadolinium enhancement at cardiovascular magnetic resonance and the biomarker carboxy‐terminal propeptide of procollagen type I had additive prognostic value 10 …”
Section: Diagnosis and Prognosismentioning
confidence: 97%
“…Late gadolinium enhancement at cardiovascular magnetic resonance and the biomarker carboxy-terminal propeptide of procollagen type I had additive prognostic value. 10 Higher levels of circulating dipeptidyl peptidase 3 (DPP3) were related with mortality in patients with cardiogenic shock and DPP3 inhibition can improve haemodynamics. 11,12 Boorsma et al 13 showed that high DPP3 levels are associated with higher renin and aldosterone concentrations and poorer outcomes.…”
Section: Biomarkersmentioning
confidence: 99%
“…In this issue of the Journal, Raafs and colleagues quantified fibrosis in 209 patients with DCM using (i) CMR non‐invasive late gadolinium enhancement (LGE), (ii) invasive endomyocardial biopsy (EMB) with determination of CVF, and (iii) circulating levels of PICP and PIIINP 10 . The authors found that PICP (but not PIIINP) was positively correlated with myocardial fibrosis as determined by CMR‐LGE (R 2 = 0.39) and by EMB‐CVF, particularly among severely symptomatic patients with reduced ejection fraction (R 2 = 0.68).…”
Section: Figurementioning
confidence: 99%
“…These molecules have been observed to be considerably correlated to the progression of myocardial fibrosis in patients with ischemic heart disease and NIDCM [ 7 , 8 ]. Additionally, their increased sera levels are able to predict MACEs in patients with HF and preserved left ventricle (LV) ejection fractions (LVEFs) [ 4 , 16 ]. However, their role in patients with NIDCM is not entirely clear.…”
Section: Introductionmentioning
confidence: 99%